Formulação de ração para juvenis de litopenaeus vanammei a partir de espécies regionais de microalgas - Varandas, Roberta Conceição Ribeiro (2016)
The carcinicultra is one of the economic activities that will grow in the Northeast. The species most cultivated shrimp is Litopenaeus vannamei. The objective of this research was to select potential microalgae strains to produce feed for juvenile shrimp Litopenaeus vannamei, and formulating rations partially replacing fishmeal by these microalgae biomass in which they were previously selected. They were chosen eight species of microalgae from the microalgae bank reef environments Laboratory and Biotechnology with Microalgae (LARBIM / UFPB): D9Z- Spirulina plantesis; D26Z-Desmodesmus; D29Z- Chlorococum sp cf hypnosporum; D39Z- Planktrothrix isothrix; D115WC- Scenedesmus acuminatus; 133WC- Lagerheimia longiseta; D359WC- Chlorella sp; D61Z- Kirchneriella lunaris. The cultivation of microalgae was held in reef environments Laboratory and Biotechnology with Microalgae (LARBIMN / UFPB) bench. the culture media were used WC and Zarrouk. The growth was accompanied by cell count and also by fluorescence "in vivo". The biomass was concentrated in centrifuge, frozen concentrates and freeze-dried. In biomasses were quantified: proteins, carbohydrates and total fat. In the chemical composition of the diets were determined moisture, ash, protein, fat, calcium and phosphorus. The results were submitted to analysis of variance (ANOVA) followed by Tukey test (P<0,05). Four experimental diets were prepared with 35% crude protein and fishmeal replaced by 40% of the biomass of microalgae three. The highest increases were registered in Desmodesmus sp., S. platensis, Chlorococcum sp cf hypnosporum, Planktothrix isothryx and Chlorella sp, which presented, respectively, the higher biomass and cell number. The second and the third and last were selected for the formulation of rations had the highest protein content. The formulated feed rations have chemical composition similar to that of commercial pet food. The data indicate that Chlorella sp., Sp cf C. hypnosporum and S. platensis may be used in partial replacement of fishmeal in diets for juvenile shrimp L. vannamei.